Flexible printable mesoscopic perovskite solar cell and preparation method thereof
By using flexible conductive films as the substrate in printable mesoscopic perovskite solar cells and setting up multi-layer structures in turn, the application limitations caused by the rigidity of traditional perovskite solar cells are solved, and flexible preparation and large-area application are achieved .
Patent Information
- Application Number
- CN202411499918.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional printable meso-perovskite solar cells use rigid conductive glass as the substrate, which cannot meet practical application needs such as lightweight, portable and wearable.
Using a flexible conductive film as the substrate of the solar device, the printed mesoscopic calcium can be achieved by sequentially setting a transparent conductive PI/ITO substrate, a TiO2 dense layer, a TiO2 mesoporous layer, a ZrO2 mesoporous layer, a conductive carbon layer and a perovskite absorbing layer. Flexible preparation of titanium-ite solar cells.
The bendable mesoscopic perovskite solar cells were successfully prepared, achieving large-area preparation and expanding practical application scenarios, and reducing production, transportation and assembly costs.
Smart Images

Figure CN119486452A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cell preparation, and relates to a printable mesoscopic perovskite solar cell on a flexible substrate and a preparation method thereof. Background Art
[0002] Perovskite solar cells (PSCs) have made great progress in the past decade due to their low cost and easy preparation. The organic-inorganic hybrid perovskites show excellent light absorption and carrier transport properties, and have attracted widespread attention with their ultra-high photoelectric conversion efficiency. Among them, printable mesoscopic perovskite solar cells (p-MPSCs) use hole-free structures and inexpensive carbon materials as back electrodes, and are prepared by screen printing technology, which solves the large-area preparation and cost problems of PSCs from the source. However, traditional p-MPSC devices use rigid material FTO conductive glass as the substrate, which cannot meet the practical application requirements such as lightweight, portable and wearable. Therefore, the application of flexible conductive substrates in p-MPSC devices is very necessary.
[0003] Chinese patent CN 107146847 A discloses a new type of all-solid-state printable perovskite solar cell based on carbon electrode, wherein a TiO2 working electrode, a ZrO2 insulating layer, a high-temperature carbon layer and a low-temperature carbon layer are sequentially printed on conductive glass by screen printing, and perovskite is added to the device by drop coating to obtain a new type of all-solid-state printable perovskite solar cell based on carbon electrode. The disadvantage of this method is that the rigid material conductive glass is used as the substrate, which is mechanically brittle and cannot meet the requirements of lightweight and portability, which will increase the production, transportation and assembly costs.
[0004] Chinese patent CN 106129251 B invented a flexible perovskite cell structure and its preparation method. The solar cell is a flexible perovskite cell obtained by sequentially depositing a metal bottom electrode, a doped electron collection layer, a perovskite layer, a hole transport layer and a transparent conductive polymer top electrode on a flexible substrate. The structure uses a high-conductivity metal as the bottom electrode to improve the conductivity of the substrate, and uses a doped electron collection layer to collect electrons, solving the problem of poor heat resistance of the flexible substrate. However, the structure of the flexible perovskite cell is completely different from that of the printable mesoscopic perovskite solar cell. It has the disadvantage of using expensive precious metal electrodes and hole output materials, and the assembly process is relatively complicated. Summary of the invention
[0005] In order to solve the limitations of existing glass conductive substrates for printable mesoscopic perovskite solar cells in practical applications, the inventors of the present invention use flexible conductive films as the substrate of solar devices to achieve flexible preparation of printable mesoscopic perovskite solar cells. Experimental results show that the preparation process disclosed in the present invention successfully prepares printable mesoscopic perovskite solar cells on flexible films. The deposited mesoporous film and perovskite material are flat and bendable on the flexible substrate, which is conducive to the large-area preparation of printable mesoscopic perovskite solar cells and the expansion of practical application scenarios.
[0006] In order to achieve the above-mentioned invention object, the present invention provides the following technical solutions:
[0007] A flexible printable mesoscopic perovskite solar cell, characterized in that the solar cell comprises a transparent conductive substrate PI / ITO, a TiO2 dense layer, a TiO2 mesoporous layer, a ZrO2 mesoporous layer, a conductive carbon layer, and a perovskite light-absorbing layer distributed in the TiO2 mesoporous layer, the ZrO2 mesoporous layer and the conductive carbon layer, which are arranged in sequence from bottom to top;
[0008] The thickness of the TiO2 mesoporous layer is 400-1000nm, the thickness of the ZrO2 mesoporous layer is 1000-3000nm, the thickness of the conductive carbon layer is 10000-50000nm, the perovskite light-absorbing layer is CH3NH3PbI3, the ITO is indium tin oxide, and the PI is polyimide.
[0009] The present invention also provides a method for preparing a flexible printable mesoscopic perovskite solar cell, characterized in that the method comprises the following steps:
[0010] (1) ultrasonically cleaning a transparent conductive PI / ITO substrate with detergent, deionized water, acetone, and ethanol in sequence and drying the substrate to obtain a pretreated substrate;
[0011] (2) diluting 300 μL of bis(acetylacetonato)diisopropyl titanate with 30 mL of ethanol and spraying the mixture on the surface of the pretreated substrate, and then annealing the substrate to obtain a dense TiO2 layer;
[0012] (3) After printing TiO2 slurry on the surface of the TiO2 dense layer obtained in step (2), annealing treatment is performed to obtain a TiO2 mesoporous layer, wherein the TiO2 slurry is prepared by mixing TiO2 and pinene alcohol, and the mass ratio of TiO2 to pinene alcohol is (1-2): (3-6);
[0013] (4) first printing ZrO2 slurry and then printing carbon slurry on the surface of the TiO2 mesoporous layer obtained in step (3), and then performing annealing treatment to obtain a ZrO2 mesoporous layer and a carbon layer,
[0014] The ZrO2 slurry is prepared by fully grinding and mixing ZrO2, ethyl cellulose and pinene alcohol, and the mass ratio of ZrO2: ethyl cellulose: pinene alcohol is (3-5): (0.5-2): (10-20).
[0015] The carbon slurry is prepared by fully grinding and mixing carbon black, graphite, ethyl cellulose and terpineol, wherein the mass ratio of carbon black: graphite: ethyl cellulose: terpineol is (3-5): (3-5): (0.5-2): (10-20);
[0016] (5) adding a perovskite precursor solution to the surface of the carbon layer obtained in step (4) and performing annealing treatment to obtain a flexible printable mesoscopic perovskite solar cell;
[0017] The perovskite precursor solution is prepared by adding 300-400 mL of N,N-dimethylformamide and 500-700 mL of dimethyl sulfoxide to 0.230 g-0.460 g of PbI2 and 0.160-0.320 g of CH3NH3I, and mixing and stirring to obtain the perovskite precursor solution.
[0018] Preferably, the detergent in step (1) is White Cat brand or Liby brand detergent.
[0019] Preferably, the annealing temperature in step (2) is 350-550° C., and the annealing time is 20-40 min.
[0020] Preferably, the temperature of the annealing treatment in step (3) and step (4) is 350-550° C., and the time of the annealing treatment is 20-40 min.
[0021] Preferably, the annealing temperature in step (5) is 70-100° C., and the annealing time is 60-180 min.
[0022] The PI / ITO conductive substrate is a commercially available product, and the manufacturer is Yingkou Youke New Materials Co., Ltd.
[0023] Beneficial Effects
[0024] The printable mesoscopic perovskite solar cell provided by the present invention has a flexible conductive PI / ITO substrate, a TiO2 dense layer, a TiO2 mesoporous layer, a ZrO2 mesoporous layer, a carbon layer and perovskite infiltrated into the mesoporous layer. The flexible printable mesoscopic perovskite solar cell provided by the present invention uses TiO2 as an electron transport layer and a carbon layer as a back electrode to replace the expensive metal electrode, and a flexible printable mesoscopic perovskite solar cell is obtained by a screen printing preparation method. Data show that the efficiency of the flexible printable mesoscopic perovskite solar cell is 1.28%, and the current density is 6.03 mA cm -2, the open circuit voltage is 0.80V and the fill factor is 26.40%. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A cell structure diagram of a flexible printable mesoscopic perovskite solar cell provided by the present invention;
[0026] Figure 2 The XRD pattern of CH3NH3PbI3 prepared in Example 1 of the present invention;
[0027] Figure 3 This is a SEM image of CH3NH3PbI3 prepared in Example 1 of the present invention;
[0028] Figure 4 This is the ultraviolet absorption graph of CH3NH3PbI3 prepared in Example 1 of the present invention;
[0029] Figure 5 The current density-voltage curve of the flexible printable mesoscopic perovskite solar cell prepared in Examples 1-3 of the present invention;
[0030] The horizontal axis represents voltage (in volts) and the vertical axis represents current density (in milliamperes per square centimeter). DETAILED DESCRIPTION
[0031] The present invention provides a flexible printable mesoscopic perovskite solar cell, comprising a transparent conductive PI / ITO substrate, a TiO2 dense layer, a TiO2 mesoporous layer, a ZrO2 mesoporous layer, a conductive carbon layer and a perovskite light absorbing layer which are arranged in sequence.
[0032] In the present invention, the thickness of the TiO2 mesoporous layer is 400-1000nm.
[0033] In the present invention, the thickness of the ZrO2 mesoporous layer is 1000-3000nm.
[0034] In the present invention, the thickness of the conductive carbon layer is 10000-50000nm.
[0035] In the present invention, the perovskite light-absorbing layer is CH3NH3PbI3.
[0036] In the present invention, the flexible conductive substrate is PI / ITO (ITO is indium tin oxide, PI is polyimide film)
[0037] The present invention ultrasonically cleans and dries the transparent conductive PI / ITO substrate with 1L of white cat detergent, 1L of deionized water, 1L of acetone and 1L of ethanol in sequence to obtain a pretreated substrate. The present invention sets the ultrasonic cleaning time to 60 minutes and the power to 400W.
[0038] After obtaining the pretreated substrate, the present invention sprays the ethanol solution of bis(acetylacetonate) diisopropyl titanate on the surface of the pretreated flexible conductive substrate to obtain a dense TiO2 layer. The ethanol solution of bis(acetylacetonate) diisopropyl titanate of the present invention preferably contains 300 μL of bis(acetylacetonate) diisopropyl titanate and 30 mL of ethanol.
[0039] In the present invention, after spraying, the sample is preferably annealed, the annealing temperature is 350-550°C, more preferably 450-500°C, and the annealing time is preferably 20-40 minutes, more preferably 25-35 minutes. In the present invention, the annealing can convert bis(acetylacetonato)diisopropyltitanate into TiO2 and can make the combination of TiO2 and the pre-treated substrate more firmly.
[0040] After obtaining the dense TiO2 layer, the present invention prints TiO2 slurry on the surface of the dense TiO2 layer and then performs annealing treatment to obtain a TiO2 mesoporous layer. In the present invention, the printing is preferably screen printing, the mesh number of the printing screen is 100-300 mesh, and the thickness of the TiO2 layer is guaranteed to be 400-1000nm. The TiO2 raw material is purchased from Great cell Solar. In the present invention, the annealing temperature of the TiO2 slurry is preferably 350-550°C, more preferably 450-500°C, and the annealing time is preferably 20-40min, more preferably 25-35min. In the present invention, the annealing treatment can form a mesoporous film from the printed TiO2 slurry.
[0041] After obtaining the TiO2 mesoporous layer, ZrO2 slurry is first printed on its surface, and then carbon slurry is printed, and then annealing treatment is performed to obtain the ZrO2 mesoporous layer and the carbon layer. Wherein, the ZrO2 slurry is made by fully grinding and mixing ZrO2, ethyl cellulose and pinene alcohol, and the mass ratio of ZrO2: ethyl cellulose: pinene alcohol is (3-5): (0.5-2): (10-20); the carbon slurry is made by fully grinding and mixing carbon black, graphite, ethyl cellulose and pinene alcohol, and the mass ratio of carbon black: graphite: ethyl cellulose: pinene alcohol is (3-5): (3-5): (0.5-2): (10-20). Printing is preferably screen printing. The mesh number of the printing screen of the present invention is 100-300 mesh, which ensures that the thickness of the ZrO2 mesoporous layer is 1000-3000nm and the thickness of the carbon layer is 10000-50000nm. In the present invention, the annealing temperature is preferably 300-450°C, more preferably 350-400°C, and the annealing time is preferably 20-40 minutes, more preferably 25-35 minutes. In the present invention, the annealing can form a mesoporous film from the printed ZrO2 slurry and carbon slurry.
[0042] After obtaining the ZrO2 mesoporous layer and the carbon layer, the present invention drips a perovskite precursor solution on the surface of the carbon layer and performs annealing treatment to obtain a flexible printable mesoscopic perovskite solar cell. In the present invention, the dripped perovskite precursor solution is preferably CH3NH3PbI3, the temperature of the annealing treatment is preferably 70-100°C, and the time is preferably 60-180min. In the present invention, the dripped perovskite precursor solution includes PbI2, CH3NH3I, N,N-dimethylformamide and dimethyl sulfoxide, and the preparation method is 0.230g-0.460g of PbI2 and 0.160-0.320g of CH3NH3I, 300-400mL of N,N-dimethylformamide and 500-700mL of dimethyl sulfoxide, and the perovskite precursor solution is obtained by mixing and stirring.
[0043] The present invention is further described below by way of examples, the purpose of which is only to provide a better understanding of the content of the present invention. Therefore, the examples cited do not limit the scope of protection of the present invention:
[0044] Figure 1 The cell structure diagram of the flexible printable mesoscopic perovskite solar cell provided by the present invention includes a transparent conductive PI / ITO substrate, a TiO2 dense layer, a TiO2 mesoporous layer, a ZrO2 mesoporous layer, a conductive carbon layer and a perovskite light-absorbing layer distributed in the mesoporous layer.
[0045] Example 1
[0046] The transparent conductive PI / ITO substrate was ultrasonically cleaned with detergent, deionized water, acetone and ethanol for 60 min in sequence and then blown dry to obtain a pretreated substrate;
[0047] 300 μL of bis(acetylacetonato)diisopropyltitanate was diluted with 30 mL of ethanol.
[0048] Spraying an ethanol solution of bis(acetylacetonato)diisopropyl titanate onto the surface of the pretreated substrate, and annealing at 500° C. for 30 min to obtain a dense TiO2 layer;
[0049] After printing TiO2 slurry on the surface of the TiO2 dense layer in the ITO / TiO2 dense layer, annealing treatment was performed at 500°C for 30 minutes to obtain a TiO2 mesoporous layer;
[0050] Firstly, ZrO2 slurry is printed on the surface of TiO2 mesoporous layer, and then carbon slurry is printed, and then annealing treatment is performed at 400°C for 30 minutes to obtain ZrO2 mesoporous layer and carbon layer;
[0051] The perovskite precursor solution was prepared by adding 0.230 g of PbI2 and 0.160 of CH3NH3I to 300 mL of N,N-dimethylformamide and 500 mL of dimethyl sulfoxide, and mixing and stirring to obtain a perovskite precursor solution. The perovskite precursor solution was dripped onto the surface of the carbon layer and annealed at 100°C for 120 minutes to obtain a flexible printable mesoscopic perovskite solar cell.
[0052] The perovskite precursor solution was dropped onto the surface of the ITO / TiO2 dense layer / TiO2 mesoporous layer and annealed at 100°C for 120 min. The obtained samples were tested by XRD, SEM and UV absorption spectrum, respectively. Figure 2 , 3 , 4, from Figure 2 The crystal structure of CH3NH3PbI3 perovskite can be seen from Figure 3 The morphology of CH3NH3PbI3 perovskite can be seen from Figure 4 The ultraviolet absorption characteristics of CH3NH3PbI3 perovskite can be seen.
[0053] The flexible printable mesoscopic perovskite solar cell prepared in this embodiment was subjected to a current density-voltage test. The test results are as follows: Figure 5 As shown in the figure, the photoelectric conversion efficiency of the flexible printable mesoscopic perovskite solar cell prepared by the present invention is 1.28%, and the short-circuit current density is 6.03 mA cm -2 , the open circuit voltage is 0.80V and the fill factor is 26.4%.
[0054] Example 2
[0055] The transparent conductive PI / ITO substrate was ultrasonically cleaned with white cat detergent, deionized water, acetone and ethanol for 60 minutes in sequence and then blown dry to obtain a pretreated substrate;
[0056] Printing TiO2 slurry on the surface of the pretreated substrate and annealing at 200°C for 30 minutes to obtain an ITO / TiO2 layer;
[0057] Firstly, ZrO2 slurry is printed on the surface of ITO / TiO2 layer, and then carbon slurry is printed, and then annealing treatment is performed at 250°C for 30 minutes to obtain ZrO2 mesoporous layer and carbon layer;
[0058] Weigh 0.460g PbI2 and 0.160g CH3NH3I respectively, add 300mL N,N-dimethylformamide and 700mL dimethyl sulfoxide, and mix and stir to obtain a perovskite precursor solution. The perovskite precursor solution is dripped on the surface of the carbon layer and annealed at 100℃ for 120min to obtain a flexible printable mesoscopic perovskite solar cell.
[0059] The flexible printable mesoscopic perovskite solar cell prepared in this embodiment was subjected to a current density-voltage test. The test results are as follows: Figure 5 As shown in the figure, the photoelectric conversion efficiency of the flexible printable mesoscopic perovskite solar cell prepared by the present invention is 1.51%, and the short-circuit current density is 7.20 mA cm -2 , the open circuit voltage is 0.84V and the fill factor is 25.05%.
[0060] Example 3
[0061] The transparent conductive PI / ITO substrate was ultrasonically cleaned with white cat detergent, deionized water, acetone and ethanol for 60 minutes in sequence and then blown dry to obtain a pretreated substrate;
[0062] Printing TiO2 slurry on the surface of the pretreated substrate and annealing at 200°C for 30 minutes to obtain an ITO / TiO2 layer;
[0063] The ZrO2 slurry was printed on the surface of the ITO / TiO2 layer, and then annealed at 250°C for 30 min to obtain a ZrO2 mesoporous layer;
[0064] PbBr2 solution (0.367 g PbBr2, add 300 mL N,N-dimethylformamide and 700 mL dimethyl sulfoxide) was dropped on the surface of the ZrO2 layer, annealed at 100°C for 120 min, immersed in CsBr methanol solution, annealed at 250°C for 10 min, and then a layer of carbon slurry was printed to obtain a flexible device based on the CsPbBr3 active layer.
[0065] The flexible printable mesoscopic perovskite solar cell prepared in this embodiment was subjected to a current density-voltage test. The test results are as follows: Figure 5 As shown in the figure, the photoelectric conversion efficiency of the flexible printable mesoscopic perovskite solar cell prepared by the present invention is 1.26%, and the short-circuit current density is 4.67 mA cm -2 , the open circuit voltage is 0.76V and the fill factor is 35.30%.
Claims
1. A flexible printable mesoscopic perovskite solar cell, characterized in that: The solar cell comprises a transparent conductive substrate PI / ITO, a TiO2 dense layer, a TiO2 mesoporous layer, a ZrO2 mesoporous layer, a conductive carbon layer, and a perovskite light-absorbing layer distributed in the TiO2 mesoporous layer, the ZrO2 mesoporous layer and the conductive carbon layer, which are arranged in sequence from bottom to top; The thickness of the TiO2 mesoporous layer is 400-1000nm, the thickness of the ZrO2 mesoporous layer is 1000-3000nm, the thickness of the conductive carbon layer is 10000-50000nm, the perovskite light-absorbing layer is CH3NH3PbI3, the ITO is indium tin oxide, and the PI is polyimide.
2. A method for preparing a flexible printable mesoscopic perovskite solar cell, characterized in that: The method comprises the following steps: (1) ultrasonically cleaning a transparent conductive PI / ITO substrate with detergent, deionized water, acetone, and ethanol in sequence and drying the substrate to obtain a pretreated substrate; (2) diluting 300 μL of bis(acetylacetonato)diisopropyl titanate with 30 mL of ethanol and spraying the mixture on the surface of the pretreated substrate, and then annealing the substrate to obtain a dense TiO2 layer; (3) After printing TiO2 slurry on the surface of the TiO2 dense layer obtained in step (2), annealing treatment is performed to obtain a TiO2 mesoporous layer, wherein the TiO2 slurry is prepared by mixing TiO2 and pinene alcohol, and the mass ratio of TiO2 to pinene alcohol is (1-2): (3-6); (4) first printing ZrO2 slurry and then printing carbon slurry on the surface of the TiO2 mesoporous layer obtained in step (3), and then performing annealing treatment to obtain a ZrO2 mesoporous layer and a carbon layer, The ZrO2 slurry is prepared by fully grinding and mixing ZrO2, ethyl cellulose and pinene alcohol, and the mass ratio of ZrO2: ethyl cellulose: pinene alcohol is (3-5): (0.5-2): (10-20). The carbon slurry is prepared by fully grinding and mixing carbon black, graphite, ethyl cellulose and terpineol, wherein the mass ratio of carbon black: graphite: ethyl cellulose: terpineol is (3-5): (3-5): (0.5-2): (10-20); (5) adding a perovskite precursor solution to the surface of the carbon layer obtained in step (4) and performing annealing treatment to obtain a flexible printable mesoscopic perovskite solar cell; The perovskite precursor solution is prepared by adding 300-400 mL of N,N-dimethylformamide and 500-700 mL of dimethyl sulfoxide to 0.230 g-0.460 g of PbI2 and 0.160-0.320 g of CH3NH3I, and mixing and stirring to obtain the perovskite precursor solution.
3. The preparation method according to claim 2, characterized in that: The detergent in step (1) is White Cat brand or Liby brand detergent.
4. The preparation method according to claim 2, characterized in that: The annealing temperature in step (2) is 350-550° C., and the annealing time is 20-40 min.
5. The preparation method according to claim 2, characterized in that: The annealing temperature in step (3) and step (4) is 350-550° C., and the annealing time is 20-40 min.
6. The preparation method according to claim 2, characterized in that: The annealing temperature in step (5) is 70-100° C., and the annealing time is 60-180 min.
Citation Information
Patent Citations
Novel carbon-based printable mesoscopic perovskite solar cell and preparation method thereof
CN111816771A
Preparation method of printable mesoscopic all-inorganic perovskite solar cell
CN117253941A